Associations of Vascular Risk Factors, APOE and TOMM40 Polymorphisms With Cognitive Function in Dementia-Free Chinese Older Adults: A Community-Based Study - Gui, Wenjun; Qiu, Chengxuan; Shao, Qi; Li, Juan (Frontiers in Psychiatry, 2021)
Objective: To investigate the associations of individual and clustering of multiple vascular risk factors (VRFs), susceptibility genes (APOE and TOMM40), and their interactions with global cognitive function in Chinese older adults. Methods: This is a cross-sectional study that included 422 participants (mean age 69.2 years, 54.3% female) in the China Longitudinal Ageing Study, who were free of dementia. Data were collected through interviews, clinical examinations, and laboratory tests. The clustering of multiple VRFs was scored by counting the number of VRFs potentially related to cognitive function. Global cognitive function was assessed with the Mini-Mental State Examination (MMSE). Data were analyzed with multiple general linear regression models. Results: Physical inactivity and diabetes were independently associated with poor global cognitive performance. Moreover, physical inactivity with APOE ε4 and TOMM40 G allele (rs2075650), and diabetes interacted with TOM40 G allele to affect cognitive function, such that having (1) both physical inactivity and APOE ε4 allele, (2) both inactivity and TOMM40 G allele, (3) both diabetes and TOMM40 G allele, compared to having neither, was significantly associated with markedly slower MMSE scores. Finally, when four modifiable VRFs (i.e., current smoking, physical inactivity, high LDL-C, and diabetes) were aggregated, an increasing number of having these factors was associated with a decreasing MMSE score in a dose-response manner. Conclusion: Having multiple VRFs or concomitant VRFs and susceptibility genes is associated with poorer cognitive performance among the Chinese elderly. These findings indicated that the treatment of modifiable VRFs, such as regular physical activity and cardiovascular risk factors management may serve as effective interventions for maintaining cognitive function among older susceptibility genes carriers.